2017
DOI: 10.3746/pnf.2017.22.4.345
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Phenolic Production and Antioxidant Activity from Buckwheat Leaves by Subcritical Water Extraction

Abstract: To enhance the production of phenolic compounds with high antioxidant activity and reduce the level of phototoxic fagopyrin, buckwheat leaves were extracted with subcritical water (SW) at 100~220°C for 10~50 min. The major phenolic compounds were quercetin, gallic acid, and protocatechuic acid. The cumulative amount of individual phenolic compounds increased with increasing extraction temperature from 100°C to 180°C and did not change significantly at 200°C and 220°C. The highest yield of individual phenolic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…PS, germinated for nine days, were kindly provided by WooYoung E&T (Jeju, South Korea). PS were dried, freeze-dried, powdered, and extracted using the pressurized hot water extraction method (modified from [ 36 ]). A 10-g sample (dry weight) of PS was mixed with 100 mL of Milli-Q water.…”
Section: Methodsmentioning
confidence: 99%
“…PS, germinated for nine days, were kindly provided by WooYoung E&T (Jeju, South Korea). PS were dried, freeze-dried, powdered, and extracted using the pressurized hot water extraction method (modified from [ 36 ]). A 10-g sample (dry weight) of PS was mixed with 100 mL of Milli-Q water.…”
Section: Methodsmentioning
confidence: 99%
“…Biological research on quercetin has been extensively documented over the past decades [ 2 ]. Recently, ISQ has gained considerable attention as a prospective compound because it has superior water solubility (95 mg/L) compared with quercetin [ 3 ]. However, the biological activity of quercetin glycosides is not well studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, these authors reported that the RA yield was lower in MAE when the extraction time was increased from 5 mins to 30 mins using high temperatures (80 • C), possibly due to the lower thermal stability of hydroxycinnamic acid derivatives. Hence, the high temperature disrupts the C-C bonds [39]. This is because the amount of energy converted to heat in the dielectric material is controlled by microwave power, which is correlated with the extraction temperature.…”
Section: Phenolic Compounds Profile and Quantificationmentioning
confidence: 99%